Rapid in situ toxicity testing with luminescent bacteria Photorhabdus luminescens and Vibrio fischeri adapted to a small portable luminometer - Masner, Petr; Javůrková, Barbora; Bláha, Luděk (Environmental science and pollution research international, 2017)
The present study demonstrates development of a rapid testing protocol based on a small portable luminometer using flash kinetic assessment of bacterial bioluminescence. The laboratory comparisons based on six model organic toxicants and two metals showed significant correlations between responses of freshwater bacteria Photorhabdus luminescens and standard marine bacterial species Vibrio fisheri. While P. luminescens was less sensitive in standard arrangements, the responses of both organisms were comparable in the newly introduced portable luminometer setup. The applicability and reproducibility of the portable luminometer protocol was further demonstrated in the assessment of 43 European wastewater effluents that were simultaneously tested for toxicity and analysed for 150 organic and 20 inorganic contaminants grouped into 13 major chemical classes. Clear association between the toxic responses in both compared bacterial species and the elevated levels of inorganic compounds (toxic metals), chlorophenols and benzotriazole anticorrosives was observed. The new protocol with a portable luminometer provides a fast (30 s) response and may be used as a tool for rapid in situ toxicity evaluation of freshwater environmental samples such as effluents.
Keywords: luminiscenční měření; luminiscence; Aliivibrio fischeri; sladká voda; Fresh Water; reprodukovatelnost výsledků; Reproducibility of Results; Photorhabdus; Photorhabdus luminescens; Time Factors; Toxicity Tests; Vibrio fisheri; testy toxicity; časové faktory; Whole effluent testing (WET); In situ testing; Portable biotest; Luminescent Measurements; Luminescence